Analysis of time-to-treatment discontinuation of targeted therapy, immunotherapy, and chemotherapy in clinical trials of patients with non-small-cell lung cancer. (22nd February 2019) - Blumenthal, G M; Gong, Y; Kehl, K; Mishra-Kalyani, P; Goldberg, K B; Khozin, S; Kluetz, P G; Oxnard, G R; Pazdur, R
Abstract: Background: Pragmatic end points, such as time-to-treatment discontinuation (TTD), defined as the date of starting a medication to the date of treatment discontinuation or death has been proposed as a potential efficacy end point for real-world evidence (RWE) trials, where imaging evaluation is less structured and standardized. Patients and methods: We studied 18 randomized clinical trials of patients with metastatic non-small-cell lung cancer (mNSCLC), initiated after 2007 and submitted to U.S. Food and Drug Administration. TTD was calculated as date of randomization to date of discontinuation or death and compared to progression-free survival (PFS) and overall survival (OS) across all patients, as well as in treatment-defined subgroups [EGFR mutation-positive treated with tyrosine kinase inhibitor (TKI), EGFR wild-type treated with TKI, ALK-positive treated with TKI, immune checkpoint inhibitor (ICI), chemotherapy doublet with maintenance, chemotherapy monotherapy]. Results: Overall across 8947 patients, TTD was more closely associated with PFS ( r  = 0.87, 95% CI 0.86–0.87) than with OS (0.68, 95% CI 0.67–0.69). Early TTD (PFS—TTD ≥ 3 months) occurred in 7.7% of patients overall, and was more common with chemo monotherapy (15.0%) while late TTD (TTD—PFS ≥ 3 months) occurred in 6.0% of patients overall, and was more common in EGFR-positive and ALK-positive patients (12.4% and 22.9%). In oncogene-targeted subgroups (EGFR positive and ALK positive), median TTDs (13.4 and 14.1 months) exceeded median PFS (11.4 and 11.3 months). Conclusions: At the patient level, TTD is associated with PFS across therapeutic classes. Median TTD exceeds median PFS for biomarker-selected patients receiving oncogene-targeted therapies. TTD should be prospectively studied further as an end point for pragmatic randomized RWE trials only for continuously administered therapies.